GAMBARAN KEMAMPUAN PERSONAL HYGIENE ANAK RETARDASI MENTAL MENURUT ORANG TUA - Suci Mandasari (Yayasan Pendidikan Medika Indonesia, 2022)
Mantal retardation is a cognitive disorder caused by the intellectual level of the child low (IQ < 70). The intellectual low in the child can deficit self care, especially persona hygiene. The purpose of this research is to determine the describtive with a sampel number of 32 elderly people. Purposive sampling is used as research sampling technique in Pekanbaru City. The measuring instrument used is a self-reliance personal hygiene questionnaire. This research used unnivariate data analysis. Data presented in the form of the frequency distribution. The result of the majority of respondents who have children with a modered mental retardation (capable of training), so that independent children perform personal hygiene as much as 25 people (78,1%), self-suffient of people (18,8%) and children ability mental retardation category less independent 1 person (3,1%). The children’s mental retardation majority always does some personal hygiene without the help of other, as it cleanses the skin and bathing, oral hygiene, hair wash, eye care, nose care and elimination (defecated/urination). Intellectual interference and motor limitations in children cause children rarely cut the nails and clean the ears independently. A child’s mental retardation (able to train) is able to maintain personal hygiene. Parents ability of personal hygiene children’s mental reterdation